IMPLEMENTASI BUDAYA SEKOLAH DALAM UPAYA PEMBANGUNAN PENDIDIKAN KARAKTER PEDULI LINGKUNGAN - Fatmah, Fatmah (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2018)
This research was to describe the implementation of school culture in developing character education for caring environment in Sekolah Dasar Negeri 163 Kecamatan Kemuning Palembang. The results obtained through observation and documentation of school culture in developing character education for caring environment had been applied well, it can be seen from the condition of class which clean, tidy, beautiful. All students were responsible, maintain and caring the schoolâs environment. In this research, there were 1-4 students disturbed their friends and play the water, so the development of character education became less effective.